Daily Physical Activities, Stress Level, and Symptoms of Abdominal Discomfort among Islamic Students - Damayati, Dwi Santy; Ilmi, Ani Auli; Mangallo, Citra; Naillah, Jumriatun; Adelia, Dhea; Ramadhan, Fitrah (Diversity: Disease Preventive of Research Integrity, 2024)
The role of students as successors to the nation's aspirations for excellence and accomplishment is of great significance, particularly for the younger generation. The weight of this responsibility induces students to neglect their physical well-being, leading to the development of gastritis diseases. Hence, this study aims to investigate the factors that are correlated with the manifestation of gastritis symptoms. The objective of this study is to investigate the correlation between daily physical activity and stress levels with the manifestation of gastritis symptoms among enrolled students at the Islamic University in Makassar. This study examines the characteristics and experiences of college students through a cross-sectional approach. The data collection was facilitated through the use of an online questionnaire. A probabilistic sample method was employed, with a total of 401 respondents included in the study. The students conducted their studies at four universities in Makassar City that are affiliated with religious institutions. The statistical analysis of the data using Spearmen's test showed that there was no statistically significant association between daily physical activity and gastritis symptoms (p value 0.074). However, a significant relationship was observed between stress levels and gastritis symptoms among Islamic students in Makassar City (p value 0.000). The findings of this investigation demonstrated a statistically significant correlation between levels of stress and the manifestation of symptoms associated with gastritis. This study proposes that the implementation of effective stress management strategies among university students is crucial in reducing the occurrence of gastritis symptoms and promoting future academic success and overall well-being.